Management of the dead in Tacloban City after Typhoon Haiyan - Ballera, Julius Erving (Western Pac Surveill Response J, 2015)
INTRODUCTION: The post-disaster management of the dead involves a series of steps including on-site identification, transfer, storage and examination of bodies and delivery to families for burial. Two weeks after Typhoon Haiyan, a team from the Department of Health (DOH) was tasked with identifying the dead in Tacloban City. METHODS: A suitable site for the collection of bodies was identified and an algorithm and standard data collection form developed. The retrieval of bodies was coordinated with the Bureau of Fire Protection personnel. Upon receipt of a body, two team members conducted a systematic external examination. Findings were documented, photos were taken and each body was assigned a unique number. RESULTS: The DOH team examined 128 bodies. Of these, the majority (86%) were complete bodies; 95% were decomposed and two were skeletonized. Two thirds (66%) were adults, sex was identifiable for 92%, and the male to female ratio was 1:1.4. The majority of adults were females. Only 11% were presumptively identified from documents in clothing; 89% remained unidentified. CONCLUSION: From the limited setting of this study, we describe the process of rapid body processing post-Haiyan. We prioritized rapid processing over more technically complicated means of identification, including DNA testing. Our protocol showed a dignified and efficient way of identifying corpses. As local and regional laboratory capacity increases in the Philippines, the collection of DNA specimens may become part of the identification algorithm.